Preoperative photography improves patient satisfaction following hallux valgus surgery. Issue 4 (June 2022) - Del Balso, Christopher; Taylor, Michel A.; Ching, Michael; Lawendy, Abdel Rahman; Sanders, David W.
Abstract: Background: Patient satisfaction is variable following hallux valgus (HV) surgery. This prospective, blinded, randomized trial endeavored to determine whether showing patients a preoperative photograph would improve satisfaction following HV corrective surgery. Methods: Adult patients undergoing HV surgery were randomized to a picture group (P) or a no picture group (NP). P-group patients were shown their preoperative photograph for 5 min at each postoperative visit. Outcome measures included the Foot Function Index (FFI), the Foot Ankle Outcome Score (FAOS), and a patient satisfaction questionnaire. Results: Twenty-nine patients were enrolled in the study (15P, 14 NP). At 3, and 6 months postoperatively, patients in the P-group were more likely to be completely satisfied with the appearance of their foot. There were no differences between groups with respect to postoperative HVA, IMA, or FFI, and FAOS scores. Conclusion: Patient satisfaction is increased following hallux valgus corrective surgery by reminding patients of the preoperative appearance of their foot through the use of photographs. Level of Evidence: Level I, randomized control trial.